Opto-Thermoelectric Tweezers: Principles and Applications - Pughazhendi, Agatian; Chen, Zhihan; Wu, Zilong; Li, Jingang; Zheng, Yuebing (Frontiers in Physics, 2020)
Opto-thermoelectric tweezers (OTET), which exploit the thermophoretic matter migration under a light-directed temperature field, present a new platform for manipulating colloidal particles with a wide range of materials, sizes, and shapes. Taking advantage of the entropically favorable photon-phonon conversion in light-absorbing materials and spatial separation of dissolved ions in electrolytes, OTET can manipulate the particles in a low-power and high-resolution fashion. In this mini-review, we summarize the concept, working principles, and applications of OTET. Recent developments of OTET in three-dimensional (3D) manipulation and parallel trapping of particles are discussed thoroughly. We further present their initial applications in particle filtration and biological studies. With their future development, OTET are expected to find a wide range of applications in life sciences, nanomedicine, colloidal sciences, photonics, and materials sciences.